APLIKASI DIETANOLAMIDA DARI ASAM LAURAT MINYAK INTI SAWIT PADA PEMBUATAN SABUN TRANSPARAN - Erliza Hambali, Tatit K Bunasor, Ani Suryani dan Giri Angga Kusumah (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTSurfactant represents one of industrial products from a downstream industry of palm. The development of surfactant has a strong prospect. Surfactant which is widely used in the personal care industry is diethanolamide (DEA). The use of DEA in a personal care  product is to improve foam and emulsion stabilizer. In this research, we used DEA for 1, 2 and 3%. The best result was achieved by using 3% of DEA. The characteristics of transparent soap were total water and evaporable substance content of 10,31%, total fatty acid of 32,84%, unsaponifiables fraction of 1,08%, insoluble matter in alcohol of 1,06%, free alkali of 0,44%, pH of 10,33, foam stability of 51,50%, emulsion stability of 98,37% and hardness of 2,95 mm/sec.Key words : dietanolamida, surfactant, transparent soap